Assessing the Impact and Failures of America’s War on Terror in the Middle East - Muhammad Shahban Sahito; Muhbat Ali Shah; Iqra (Progressive Research Journal of Arts & Humanities (PRJAH), 2023)
This research paper critically analyses how the United States aided Jihadists and supported terrorists and paramilitary organisations during the Cold War. It further defines Jihadists in the United States. Despite this, it discusses US aid to some authoritarian governments that have used state terrorism as a means of repression in the Middle East and US supports for non-state terrorists. Apart from that, it elaborates on US foreign policy regarding weapons, training, and extensive financial and logistical support for terrorist organisations in the Middle East. Further, it explains how radical Islamist terrorism is a serious threat and how many terrorist groups operate in the Middle East. In addition, this article discusses the causes of Islamist terrorism. The paper argues that if authoritarianism is not the cause of Islamist terrorism then what other factors have contributed to it? In addition, the research examines the challenges of American foreign policy in the Middle East in the fight against terrorism. This study argues that the war on terror has failed because of two main reasons discussed in the research paper. It also considers how American foreign policy in the Middle East has been complex and has evolved over the years.